Institutional determinants and entrepreneurial action - Crnogaj, Katja; Bradač Hojnik, Barbara (Faculty of Economics, Split, 2017)
The paper examines the effect of specific institutional factors on entrepreneurial activity. In the course of the examination, we encounter various viewpoints regarding entrepreneurship and different needs of national politics. The research objective is to determine whether institutional factors influence early-stage entrepreneurial activity. There is a broad array of opinions on appropriate set of factors that influence the entrepreneurship processes, on ways of their influence and on differentiating between the developed and less developed countries. Therefore, we examined the defined research hypothesis in the light of 24 countries (Argentina, Belgium, Brazil, Chile, Columbia, Croatia, Denmark, Finland, France, Greece, Hungary, Island, Italy, Japan, Latvia, Netherlands, Norway, Peru, Russia, Slovenia, Spain, United Kingdom, Uruguay and USA), in the period between the years 2006 and 2010 (24 countries * 5 years = 120 observations). The data was obtained from Global Entrepreneurship Monitor (GEM) database and complemented with data from other international sources such as Heritage Foundation, among others. With econometrics business methods, we determined that greater economic freedom in the institutional context of a country affects the extension of productive entrepreneurship, while the individual's decision for the entrepreneurship is conditioned significantly by the prevailing cultural and social norms. U ovom se radu analizira djelovanje specifičnih institucionalnih čimbenika na poduzetničku aktivnost, pri čemu se u obzir uzimaju različiti pogledi na poduzetništvo i potrebe nacionalne politike. Cilj istraživanja je utvrditi utječu li institucionalni čimbenici na ranu poduzetničku aktivnost. Pritom postoji veliki broj različitih mišljenja o odgovarajućem broju čimbenika, koji utječu na poduzetnički proces, kao i prirodi njihova utjecaja te razlikama između više i manje razvijenih zemalja. Stoga smo analizirali svoju hipotezu s obzirom na podatke iz 24 zemlje (Argentine, Belgije, Brazila, Čilea, Kolumbije, Hrvatske, Danske, Finske, Francuske, Grčke, Mađarske, Islanda, Italije, Japana, Latvije, Nizozemske, Norveške, Perua, Rusije, Slovenije, Španjolske, Velike Britanije, Urugvaja i SAD-a), za period između 2006. i 2010. godine, a što čini ukupno 120 opažanja. Podaci su preuzeti iz baze podataka istraživanja Global Entrepreneurship Monitor (GEM) i dopunjeni podacima iz međunarodnih izvora, kao što je Heritage Foundation. Korištenjem ekonometrijskih modela, utvrđeno je da razina ekonomske slobode, u institucionalnom kontekstu, utječe na povećanje produktivnog poduzetništva. Na individualne odluke o ulasku u poduzetništvo, pak, značajno djeluju prevladavajuće kulturne i društvene norme.